PENGARUH FACTOR SOCIAL, STORE ENVIRONMENT DAN SHOPPING LIFESTYLE TERHADAP IMPULSIF BUYING KONSUMEN MUSLIM PADA MATAHARI DEPARTMENT STORE ROYAL PLAZA SURABAYA - Ayuni, Devi; Fikriyah, Khusnul (Universitas Negeri Surabaya, 2024)
We often encounter impulse purchases in everyday life. This research aims to identify the influence of social factors, store environment and shopping lifestyle on impulsive buying of Muslim consumers at Matahari Department Store Royal Plaza Surabaya. This research uses a quantitative research method with an associative approach and uses a non-probability sampling technique with a purposive sampling technique. The type of data in this research uses primary data and is collected through distributing questionnaires with Likert scale measurements. The analysis technique used to test the hypothesis uses SmartPLS 4. The research results show that partially the social factors and shopping lifestyle variables have a positive and significant effect on consumer impulse buying. Meanwhile, the store environment variable has no significant effect on consumer impulse buying. This shows that consumers need recommendations from others to buy a product and make purchases that suit their lifestyle and financial capabilities. Recommendations from others are important because they increase consumer trust in the product.